Manifestations of Hidden Curricular Messages in the PGDT Program: Covert Tasks in Focus - Wudu, Haileyesus (Bahir Dar Journal of Education, 2019)
This study describes the experiences of student-teachers in the Post Graduate Diploma in Teaching (PGDT) program. The aim was to explore the hidden curricular messages within the program, covert tasks in focus, by answering two central questions: 1)What do student-teachers’ experiences in the PGDT program tell us about their task compliance in their training 2) Do student-teachers’ task compliance vary significantly with their background characteristics? Exploratory sequential mixed methods study was conducted in three public universities over the course of three academic terms. Data consisted of transcribed interviews and questionnaire survey. In the first phase of the study, data was collected and analyzed relying on the assumptions of phenomenological inquiry from purposively selected 25 student-teachers (male=15 and female=10). In the second stage, survey was conducted on a relatively large sample size consisting 356 student-teachers (male=216 and female=140) selected using systematic random sampling. The qualitative data were transcribed, coded and interpreted thematically; and quantitative data was reduced into descriptive statistics such as t-tests and one way ANOVA. Main findings from this study indicated that, various elements of covert tasks were manifested in the PGDT program and these elements of covert tasks attested superficial task compliance of the trainees. The results also indicated that the differences in mean scores across student-teachers background characteristics, as measured by the Task Compliance Rating Scale, were not found statistically significant. Therefore, this study raises questions and concerns about the vigor of PGDT program in enabling student-teachers exhibit the minimum competency thresholds espoused by the secondary school pre-service teacher education program.